Report of the Committee against Torture - United Nations (United Nations, 2017)
This is the annual report of the Committee against Torture on the fifty-fifth Session (27 July-14 August 2015), the fifty-sixth Session (9 November-9 December 2015), and the fifty-seventh Session (18 April-13 May 2016).